Análise da autonomia das populações tradicionais no manejo comunitário de recursos florestais madeireiros em unidade de conservação da Amazônia - PACHECO, Jéssica dos Santos (Universidade Federal do Pará, 2017)
The present study aim to analyze the degree of autonomy of the traditional populations in the timber community forest management (CFM) in federal protected areas (UC) of the Brazilian Amazon. To do so, it was evaluated (1) the perception of stakeholders in two UCs and (2) the legal instruments and regulatory provisions that could influence this autonomy. In total, 111 stakeholders from the RESEX Verde Para Sempre (VPS) and the Tapajós National Forest (FLONA Tapajós) were interviewed among the Government, Community and Partner Organizations segments. The perception was evaluated by SWOT analysis and 5-level Likert scale satisfaction questionnaires. Relevant documents on the MFC used in the UCs (minutes, reports, diagnoses, among others) were also evaluated. Decision makers from the main federal environmental agencies in Brasilia were also interviewed. The results showed that the dependence of annual permits from the ICMBio and the administrative procedures of the MFC directly interfere in the autonomy of the traditional populations, although they are of exclusive obligations of the environmental agencies. In the initiatives studied, there was relative satisfaction on the autonomy of the traditional populations. However, governmental interference occurred in both cases. In the FLONA Tapajós, the governmental administrative structure has affected the freedom of the community to define its productive choices, mainly due to the outdated management plan of the UC. Also, the autonomy to organize and manage forest production has been restricted at RESEX VpS, both due to its financial dependence on partner organizations and the time lapse until management license is approved. The legal instruments and regulatory provisions of the MFC in UC are the main inducers of this scenario. It was verified that these instruments are constituted by rules of territorial, procedural and technical dimensions that, to a greater or lesser extent, interfere in the community autonomy in the management of the forest resource, in the process of obtaining the MFC license, and in the techniques required in the activity. The failure to comply with the legal determination to create differentiated provisions of sustainable forest management plans adapted to community needs has conditioned traditional communities to standardized technical requirements, to the detriment of the constitutional and legal recognition of their livelihood rights. Some priority changes in the regulations were identified and proposed in this study. It was concluded that the simplification of some instruments could increase the degree of autonomy in the timber CFM allowing its multiplication in the Amazon region, while ensuring, at the same time, a balanced and effective control by the State over public forests in common ownership.